METODE PENDEKATAN HUKUM FILOSOFIS TERKAIT BENTUK PENYELESAIAN SENGKETA EKONOMI SYARIAH - Riski Ari Wibowo; Fakhrul Ardiyan; Irwan Triadi (CV. ADIBA AISHA AMIRA, 2025)
The philosophical legal approach is a method of legal analysis that focuses on the values, morals, and objectives of law. In the context of resolving Sharia economic disputes, this approach is crucial for understanding the philosophical basis of Islamic law and its application within the Indonesian national legal system. This study aims to describe how a philosophical legal approach can be used to analyze and develop a model for resolving Sharia economic disputes in accordance with the principles of substantive justice and the maqasid al-syarī'ah (objectives of sharia). The method used in this study is a juridical-philosophical approach with qualitative analysis. The results of the study indicate that a philosophical legal approach can strengthen the integration between Sharia law and positive law in resolving Sharia economic disputes, particularly in the context of religious courts and Sharia arbitration. This approach prioritizes a balance between legal certainty, expediency, and spiritual justice, which are the spirit of the Islamic legal system.